2003
DOI: 10.1002/polb.10391
|View full text |Cite
|
Sign up to set email alerts
|

In situ polymerization of silicic acid in polyethylene–octene elastomer: Properties and characterization of the hybrid nanocomposites

Abstract: Silicic acid produced from sodium metasilicate hydrate and metallocene polyethylene-octene elastomer (POE) were chosen as the ceramic precursor and the continuous phase, respectively, for preparation of new hybrids by an in situ sol-gel process. To obtain a better hybrid, the acrylic acid-grafted polyethylene-octene elastomer (POE-g-AA) prepared in our laboratory and used as the continuous phase was also investigated. Characterizations of POE/SiO 2 and POE-g-AA/SiO 2 composites were performed by Fourier transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
30
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 36 publications
6
30
0
Order By: Relevance
“…The glass transition temperature (T g ) of the hybrid composites is associated with a cooperative motion of long-chain segments, which may be hindered by the titania network. 7 Therefore, as expected, both PCL/ TiO 2 and PCL-g-AA/TiO 2 recorded higher glass tran- sition temperatures than pure PCL (Table III). It was also found that the enhancement in T g for PCL-g-AA/ TiO 2 hybrids was more significant than that for PCL/ TiO 2 hybrids.…”
Section: Thermal Stability Of Hybrids (Dsc and Tga Tests)supporting
confidence: 79%
See 3 more Smart Citations
“…The glass transition temperature (T g ) of the hybrid composites is associated with a cooperative motion of long-chain segments, which may be hindered by the titania network. 7 Therefore, as expected, both PCL/ TiO 2 and PCL-g-AA/TiO 2 recorded higher glass tran- sition temperatures than pure PCL (Table III). It was also found that the enhancement in T g for PCL-g-AA/ TiO 2 hybrids was more significant than that for PCL/ TiO 2 hybrids.…”
Section: Thermal Stability Of Hybrids (Dsc and Tga Tests)supporting
confidence: 79%
“…This result may be due to the formation of ester groups through the reaction between carboxylic acid groups of PCL-g-AA and titanium-bonded isopropyl groups of the titania network. 7,32 Furthermore, a comparison of the PCL and PCL/ TiO 2 (10 wt %) spectra shows new peaks between 3000 and 3800 cm Ϫ1 (Fig. 1) and at 821 and 1622 cm Ϫ1 (Fig.…”
Section: Infrared Spectroscopymentioning
confidence: 94%
See 2 more Smart Citations
“…The peak at 2y ¼ 18.08 may be due to the formation of an ester carbonyl functional group, as described in the discussion of FTIR analysis, and is similar to that reported by Wu and Liao. 36 Condensation between POE-g-AA and MWNTs-COCl also caused the reappearance of a peak at 2y ¼ 19.88, which is due to recovery of POE characteristics with the consumption of AA in the POE-g-AA. Because the peaks at 2y ¼ 26.18 and 43.18 in the spectrum of MWNTs-COOH [ Fig.…”
mentioning
confidence: 95%